2023
DOI: 10.3389/fphar.2023.1085509
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenosides, potential TMPRSS2 inhibitors, a trade-off between the therapeutic combination for anti-PD-1 immunotherapy and the treatment of COVID-19 infection of LUAD patients

Abstract: Background: Acting as a viral entry for coronavirus to invade human cells, TMPRSS2 has become a target for the prevention and treatment of COVID-19 infection. Before this, TMPRSS2 has presented biological functions in cancer, but the roles remain controversial and the mechanism remains unelucidated. Some chemicals have been reported to be inhibitors of TMPRSS2 and also demonstrated other pharmacological properties. At this stage, it is important to discover more new compounds targeting TMPRSS2, especially from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Santoni et al evaluated the treatment outcomes of cancer patients, including non-small cell lung cancer, urothelial cancer, renal cell carcinoma and melanoma, receiving immune checkpoint inhibitors (ICIs) alone or in combination with other agents versus control and found that the use of ICIs may significantly increase the chances of disappearance of all target lesions in response to therapy versus control treatments [ 9 , 10 , 11 , 12 ]. Additionally, previous studies have revealed that tumor-infiltrating lymphocytes (TILs) play an important role in modulating chemotherapy response and improving clinical prognosis in various types of cancer [ 13 , 14 , 15 ], such as tumor-infiltrating neutrophils (TINs) and tumor-associated macrophages (TAMs) [ 16 , 17 , 18 ], and they also associate with the prognosis [ 19 , 20 , 21 , 22 ]. As a result, it is a critical and urgent requirement to understand the immunophenotypes of tumor-immune interactions and identify new immune therapy targets for renal cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Santoni et al evaluated the treatment outcomes of cancer patients, including non-small cell lung cancer, urothelial cancer, renal cell carcinoma and melanoma, receiving immune checkpoint inhibitors (ICIs) alone or in combination with other agents versus control and found that the use of ICIs may significantly increase the chances of disappearance of all target lesions in response to therapy versus control treatments [ 9 , 10 , 11 , 12 ]. Additionally, previous studies have revealed that tumor-infiltrating lymphocytes (TILs) play an important role in modulating chemotherapy response and improving clinical prognosis in various types of cancer [ 13 , 14 , 15 ], such as tumor-infiltrating neutrophils (TINs) and tumor-associated macrophages (TAMs) [ 16 , 17 , 18 ], and they also associate with the prognosis [ 19 , 20 , 21 , 22 ]. As a result, it is a critical and urgent requirement to understand the immunophenotypes of tumor-immune interactions and identify new immune therapy targets for renal cancers.…”
Section: Introductionmentioning
confidence: 99%